2012
DOI: 10.2478/v10153-011-0094-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aliskiren on Blood Pressure and Myocardial Function Assessed by Global Longitudinal Strain in Patients with Arterial Hypertension and Diastolic Dysfunction

Abstract: OBJECTIVE: To evaluate the effects of aliskiren on blood pressure and myocardial function assessed by global longitudinal strain in patients with uncontrolled arterial hypertension. PATIENTS AND METHODS: Forty-fi ve patients were included in the study (29 males, 16 females, mean age 58.7 ± 12.4 years) with BP > 140/90 mmHg despite treatment with combined antihypertensive therapy and echocardiographic data for diastolic dysfunction: Е/Е'ratio ≤ 8, Е/А ratio < 0.8, deceleration time (DT) > 200 msec. Aliskiren (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…We observed an increased ejection fraction, but no significant reduction of E/A in elderly hypertensive patients with aliskiren treatment. Similarly, recent studies demonstrated no effect of adding aliskiren to other types of antihypertensive drugs on E/A in uncontrolled hypertensive patients (21). The discrepancy between animal and human studies may be attributable to a much higher dose (mg/kg) of aliskiren used in animals than that administered in humans.…”
Section: Left Ventricular Functionmentioning
confidence: 97%
“…We observed an increased ejection fraction, but no significant reduction of E/A in elderly hypertensive patients with aliskiren treatment. Similarly, recent studies demonstrated no effect of adding aliskiren to other types of antihypertensive drugs on E/A in uncontrolled hypertensive patients (21). The discrepancy between animal and human studies may be attributable to a much higher dose (mg/kg) of aliskiren used in animals than that administered in humans.…”
Section: Left Ventricular Functionmentioning
confidence: 97%
“…For patients with increased LVM, we typically re-assess LVM on an annual basis until normalization of LVM is noted. Studies in adults have demonstrated that treatment of hypertension results in significant improvements in diastolic function ( 83 ) and systolic strain ( 84 ). Improvement in cardiac function with treatment have also been seen in youth as increased shortening fraction was demonstrated in a pediatric patients with chronic kidney disease who underwent intensive BP treatment ( 85 ).…”
Section: Non-invasive Assessments Of Cardiac and Vascular Target Orgamentioning
confidence: 99%